"My Mother Wants Me to Jiaru-haomen (Marry Into a Rich and Powerful Family)!": Exploring the Pathways to "Altruistic Individualism" in Chinese Professional Women's Filial Strategies of Marital Choice. (7th January 2015) - To, Sandy
In an era of individualization, Chinese individuals often have to face the challenge of balancing their personal choices with their filial obligations. While a host of "filial strategies" are well-documented in traditional areas of filial contention such as elderly care and relating with in-laws, there are none in the area of sheng nü or "leftover women's" marital choices. This study sets out to explore the "marital filial strategies" of unmarried Chinese professional women who face filial contentions in their "marriage timing" and "partner choice." It was found that the combination of the filial strategies of "deferring" to parents' matchmaking demands, followed by "negotiation" of one's partner choice, led to the ideal condition of "altruistic individualism" that "combined personal freedom with engagement with others." On a wider level, sheng nü's filial strategies of marital choice could serve as an exemplar for all modern Chinese individuals who strove to conduct congenial filial relationships without compromising their own ideals.